Linking Mechanism of Inward FDI and Bilateral Exchange Rate - Tabassam, Samra; Ali, Maisam (Asian Development Policy Review, 2019)
This research study examines the impact of the bilateral exchange rate (BEXR) on FDI inflow into the South Asian countries, i.e. Pakistan, India, Bangladesh, Sri Lanka, Nepal, Bhutan, Afghanistan, and the Maldives. Panel data technique is used to investigate the results while using the data from 2004 to 2016. Moreover, static panel data technique cannot be used to provide robust results as the causality of variables challenge the model. To resolve the problem dynamic panel model (GMM) is used. The investigated results show a mixed trend. OLS Model showed that BEXR is negatively related (when significant) to FDI inflow. Similarly, the static panel model showed that BEXR has a negative relationship with FDI inflow, but the relationship is not significant. However, the results estimated by Dynamic panel model (GMM) are different from the previous models. It showed that BEXR has a positive relationship with FDI inflow. The positive relationship of BEXR with FDI inflow is in line with the theories that strong currency discourages FDI into the country while weak currency motivates FDI into the country. The exchange rate in emerging economies (South Asia) is rather lower that can be availed by MNEs (foreign investors) to invest in these countries. Similarly, the study can help the policy makers of these countries to enhance FDI into the country as FDI boosts the economy of the country.